Dziedzictwo niechciane. Walka pamięci w tetralogii śląskiej Evy Tvrdej - Pospiszil, Karolina (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The paper discusses the issue of (national/ethnical) cultural heritage and the conflict between hegemonic politics of memory and collective memory of cultural/ /ethnic minority based on the example of Silesian tetralogy by Eva Tvrdá, a writer tied to the Hlučín Region. Some of novels characters betray their families and community choosing to assimilate into Czech or German society, yet find full assimilation impossible, and identity cannot been reestablished. The constant feeling of being empty and incomplete becames a heritage, which Tvrda‘s characters pass down to the next generation.
Keywords: Hlučín Region; memory; identity; Upper Silesia; Eva Tvrdá; cultural heritage; minority